Before the Most Holy = - Mary Loyola, Mother, 1845-1930; Thurston, Herbert, 1856-1939 (Salt Lake City, UT : Project Gutenberg, 2025)
"Before the Most Holy = (Coram Sanctissimo)" by Mother Mary Loyola is a collection of Catholic devotional meditations written in the early 20th century. Centered on Eucharistic adoration, it offers intimate, practical guidance for (3z(Bvisits(3y (Bto the Blessed Sacrament and for cultivating a living friendship with Christ present in the tabernacle. Mixing brief prose meditations with occasional verse, it encourages praise, contrition, thanksgiving, and confident petition, especially amid distraction and spiritual dryness. The opening of the work frames the practice historically through an editor$1 (Bs preface, noting how visits to the Blessed Sacrament developed gradually and explaining that the book$1 (Bs aim is to help ordinary people pray simply and sincerely. The first chapters then model conversational prayer: urging frequent, affectionate visits to Jesus, translating everyday concerns into dialogue with Him, and welcoming readers to bring worries, defeats, and small victories to His Heart. Themes include praise in trial, readiness to share Christ$1 (Bs chalice ((3z(BPossumus(3y(B), His desire for companionship in the tabernacle, bringing practical cares into prayer ((3z(BWhat things?(3y(B), trust in faith over feelings, resilience after failure and gratitude after grace, and the courage to follow truth. Interwoven poems and reflections move through neglect, night adoration, Divine providence, the lavish (3z(Bimprovidence(3y (Bof Eucharistic love, inner transformation, darkness and dereliction met with filial trust, the gravity of His Second Coming, and a final turn to see the world sanctified by Christ$1 (Bs hidden Presence. (This is an automatically generated summary.)s
Release date is 2025-09-16
Ed Foster, Tim Lindell and the Online Distributed Proofreading Team at https://www.pgdp.net (This file was produced from images generously made available by The Internet Archive/Canadian Libraries)
Keywords: Meditations; Lord's Supper -- Prayers and devotions -- English